Cultural values shape the expression of self-evaluative social emotions - von Suchodoletz, A; Hepach, R (Springer Nature, 2021)
Social emotions are key to everyday social life and therefore shaped by cultural values in their expression. Prior research has focused on facial expressions of emotions. What is less clear, however, is the extent to which cultural values shape other modalities of emotional expression. In the present study, we applied a novel paradigm using depth sensor imaging technology to capture changes in participants' body posture in real time. We aimed to (1) identify the nuances in the postural expression that are thought to characterize social emotions and (2) assess how individual differences in cultural values impact the postural expression of emotions. Participants in two separate studies were 132 undergraduate college students whose upper-body postural expansion was recorded after they recalled emotion episodes. Positive emotions elevated participants' upper-body posture whereas negative emotions resulted in lowered upper-body posture. The effects on changes in upper-body posture were moderated by participants' self-ratings of the vertical and horizontal dimensions of individualism and collectivism. The findings provide initial evidence of the nuances in the way cultural values influence the postural expression of emotions.